Foreign experience in evaluating the implementation of state programs - Esetov , Е.Zh. (BUKETOV BUSINESS REVIEW, 2019)
In the article the main methods and tools for evaluating the implementation of budget programs in developed countries are discussed, to assess the effectiveness of the implementation of state programs and to search for new criteria for their assessment in the Republic of Kazakhstan. The main problems of assessing the implementation of government programs over the last 50 years in developed countries of the world are highlighted. The rating systems for assessing the budget programs of countries such as Australia, South Korea, France, Canada, the United States and Russia are systematized. The main indicators characterizing the effectiveness of the implementation of state programs in these countries are compared. The features of using the PART tools and its four blocks of issues, the adoption of the GPRAMA modernization act, the use of the RAA in evaluating the effectiveness of the implementation of budget programs in the United States, as well as the program-targeted management of budget programs in Australia are noted. The experience of Russia on the feasibility of evaluating the effectiveness of the implementation of budget programs, both at the development stage and at the completion stage, is emphasized. The need for the redistribution of budget funds from inefficient state to effective one was noted. It is concluded that in developed countries such as: Australia, South Korea, France, Canada, the United States, implementing the state programs contribute to the development of the national economy, small and medium businesses and increase of the social potential of society and create material benefits for every citizen and country on the whole.